Dexamethasone and sex regulate placental glucocorticoid receptor isoforms in mice. Issue 2 (August 2017) - Cuffe, James S M; Saif, Zarqa; Perkins, Anthony V; Moritz, Karen M; Clifton, Vicki L
Abstract : Maternal dexamethasone exposure in the mouse impairs placental development and programs adult disease in a sexually dimorphic manner. Glucocorticoids bind to different glucocorticoid receptor (GR) isoforms to regulate gene transcription and cellular signaling. We hypothesized that sexually dimorphic placental responses to glucocorticoids are due to differences in GR isoforms present in the placenta. Pregnant C57Bl6 mice were exposed to saline or dexamethasone from E12.5 until E14.5 (1 µg/kg/h) before the collection of placentae. Cytoplasmic and nuclear protein fractions were extracted from placentae of male and female fetuses for Western blot analysis of GR isoforms. Eight known isoforms of the GR were detected in the mouse placenta including the translational isoforms GRα-A, B, C and D1–3 and the splice variants GRA and GRP. The expression of GRA, GRP and each of the GRα isoforms were altered by dexamethasone in relation to fetal sex and cellular location. Placentae of female fetuses had higher GRα-A and GRP expression in the cytoplasm than males, and GRα-C was more highly expressed in the nucleus of females than that in males. Dexamethasone significantly increased the cytoplasmic expression of GRα-A, but reduced the expression of GRα-C in placentae of males. Dexamethasone increased the expression of the GRα-C-regulated genes Sgk1 and Bcl2l11, particularly in females. The cleaved caspase-3 staining in placental sections indicated GRα-C may mediate sex differences in dexamethasone-induced apoptosis. These findings may underlie the sex-specific placental adaptations that regulate different growth profiles in males and females and different risks for programmed disease outcomes in offspring.